Pengaruh Brand Ambassador, Brand Image, dan Kualitas Produk Terhadap Keputusan Pembelian Pada Pengguna Sepatu Ventela di Kecamatan Surabaya Gubeng - Afifah, Farhanah Dhia (Research Journal of Social Science and Economics, 2025)
The phenomenon of competition that dominates the business life of the sneaker industry is currently generated by many national and international shoe brand companies. From the results of the data, competition for local shoe brands and international shoe brands in the sneaker industry is very tight in 2017-2023. In this quantitative investigation, a google form questionnaire was used to collect data. Consumers in the Gubeng District of Surabaya City who wear ventella shoes are the focus of this research. A sample of 96 respondents matching specified criteria was selected using a non-probability, purposive selection method. This research used the t-test, F-test, and Coefficient of Determination (R2) in addition to the validity test, rehabilitation test, linear test, normalcy test, multicollinearity test, and heteroscedasticity test. According to the analysis of the Simultaneous test, the Purchase Decision of ventella shoe customers in the Gubeng sub-district of Surabaya was significantly impacted by Brand Ambassadors, Brand Images, and Product Qualities.